Coffee consumption and the risk of Venous Thromboembolism – The Tromsø study - Enga, Kristin (Universitetet i Tromsø, 2011)
Background: Several studies have investigated the association between coffee consumption and cardiovascular disease, but little is known about coffee intake and risk of venous thromboembolism (VTE). Objective: The aim of this prospective cohort study was to investigate the association between coffee consumption and risk of incident VTE in a general population. Methods: Information about coffee consumption habits was obtained by a self-administered questionnaire in 26 755 subjects, aged 25-97 years, who participated in the fourth survey of the Tromsø study (1994-95). Incident VTE events were registered until the end of follow-up, 1 September 2007. Results: There were 462 incident VTE events (1.60 per 1000 person-years, 95% CI: 1.46-1.75) during a median of 12.5 years of follow-up. A daily consumption of 3-4 cups was borderline associated (HR: 0.70; 95% CI: 0.48-1.02), while 5-6 cups (HR: 0.67; 95% CI: 0.45-0.97) of coffee was significantly associated with reduced risk of VTE compared to coffee abstainers in multivariable analysis adjusted for age, sex, BMI, smoking status, physical activity, diabetes, history of cardiovascular disease and cancer. Similar risk estimates were found for provoked and unprovoked VTE, and in sex-stratified analyses. Conclusion: Our findings suggest a possible U-shaped relation between coffee consumption and VTE, and that moderate coffee consumption may be associated with reduced risk of VTE. However, more studies are needed to establish whether a moderate coffee consumption is inversely associated with the risk of VTE.